Peningkatan Keterampilan Membaca Nyaring Siswa Melalui Model Pembelajaran Make A Match Mata Pelajaran Bahasa Indonesia Kelas I SDN 1 Mataram - Rosyidah, Umdatur; Triwahyuni, Intan; Musaddat, Syaiful (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study is a classroom-based study that aims to improve the reading aloud skills of Indonesian language subjects among SDN 1 Mataram Grade I students through the use of the “Make A Match” teaching model. The subjects of this study were the class I students of SDN 1 Mataram, a total of 27 students, of which 9 were male students and 18 were female students. This study will be conducted using two cycles, each cycle. The results of this study are to improve the reading aloud ability of Indonesian language subjects among SDN 1 Mataram Grade I students through the use of the Make a Match teaching model from Cycle I. Based on the above chart, it shows the average value. The average reading aloud skill of students in Pre-Cycle without the Build a Car Collaborative model was 56%, Cycle 1 showed an increase with a 70% score, then Cycle II saw an 11% increase with a score of 81%. The results of the above study prove that there is an increase in the application of the Make a Machine cooperative learning model for the reading aloud skills of Class I students in SDN 1 Mataram. Due to the above findings, teachers are advised to select and use appropriate teaching models and media when teaching Indonesian, especially in the aspect of reading aloud.